Internalization of Religious Character Education Program For Children With Special Needs in Islamic Religious Education (PAI) Learning at SD it Darul Mukhlisin Aceh Tamiang - Repi, Predi Ari; Salminawati, Salminawati; Rohman, Fatkhur (FKIP - Universitas Riau, 2025)
This study examines in depth the internalization of religious character education programs for Children with Special Needs (ABK) in Islamic Religious Education (PAI) learning at SD IT Darul Mukhlisin Aceh Tamiang. The background of this study is based on the importance of instilling religious values ​​that are not only part of cognitive knowledge, but also part of daily attitudes and behaviors, especially for ABK students who face limitations in understanding and applying religious values ​​independently. SD IT Darul Mukhlisin as an Integrated Islamic school took the initiative to implement an inclusive learning program with a religious character-based approach to answer these needs. This study uses a descriptive qualitative approach with a case study method. Data collection techniques are carried out through participatory observation, in-depth interviews with special assistant teachers, principals, parents of students, and documentation of learning activities and religious programs. The data analysis process is carried out through the stages of data reduction, data presentation, and drawing conclusions.The results of the study showed that internalization of religious character values ​​was carried out through a number of integrated programs, such as the habituation of daily worship (prayer, prayer, and reading the Qur'an), moral training through ethical case simulations, spiritual guidance by Islamic Religious Education teachers, and routine religious activities such as dhikr together and ablution and prayer training. The approach used in learning is adjusted to the needs and potential of individual ABK students through visual methods, direct practice, use of simple language, and a friendly and inclusive classroom atmosphere. Learning strategies also involve collaboration between teachers, parents, and experts to ensure a holistic approach to children's character education.